Economic welfare - Cowen, Tyler (Cheltenham, UK ; Northampton, MA, USA : Edward Elgar, 2000)
This book presents an important collection of leading writings in the field of policy evaluation. It focuses on the conceptual issues behind welfare economics, drawing upon contributions from economics, moral philosophy and social philosophy.
Includes bibliographical references and index.
osc 24/01/2014
Loans
Keywords: Welfare economics